If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x-1)=4(x+2)-x
We simplify the equation to the form, which is simple to understand
8(x-1)=4(x+2)-x
Reorder the terms in parentheses
+(+8x-8)=4*(x+2)-x
Remove unnecessary parentheses
+8x-8=+4+*(+x+2+)-x
Reorder the terms in parentheses
+8x-8=+(+4x+8)-x
Remove unnecessary parentheses
+8x-8=+4x+8-x
We move all terms containing x to the left and all other terms to the right.
+8x-4x+1x=+8+8
We simplify left and right side of the equation.
+5x=+16
We divide both sides of the equation by 5 to get x.
x=3.2
| 4(5x+4)=20x+16 | | (13x)-4=(x-8) | | 3(x+1)-5=3x-3 | | 7-(4y-3)=4-5y | | .20x+.45(70)=45.5 | | x^2-6x-230=0 | | 1.3t+3(t+8.2)=375 | | 7t+8t=45 | | 2(2r+5)+1=5-3(3-r) | | 4(x-1)=2(x+2)-x | | 5v=-2v-3v | | -4y-12=3y+16 | | 9(x+8)=8(x-8)+x | | 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 | | 8y-2=-6y+50 | | -10=2+2.4w | | 5.8-1.4=16 | | 9(g+2)-4=7g+3(3g+8) | | 7(st)=(7s)t |